Relationship Between Fear of COVID-19, Conspiracy Beliefs About Vaccines and Intention to Vaccinate Against COVID-19: A Cross-National Indirect Effect Model in 13 Latin American Countries - Caycho-Rodríguez, Tomás (2023)
The present study explored the predictive capacity of fear of COVID-19 on the intention to be vaccinated against COVID-19 and the influence in this relationship of conspiracy beliefs as a possible mediating psychological variable, in 13 Latin American countries. A total of 5779 people recruited through non-probabilistic convenience sampling participated. To collect information, we used the Fear of COVID-19 Scale, Vaccine conspiracy beliefs Scale-COVID-19 and a single item of intention to vaccinate. A full a priori Structural Equation Model was used; whereas, cross-country invariance was performed from increasingly restricted structural models. The results indicated that, fear of COVID-19 positively predicts intention to vaccinate and the presence of conspiracy beliefs about COVID-19 vaccines. The latter negatively predicted intention to vaccinate against COVID-19. Besides, conspiracy beliefs about COVID-19 vaccines had an indirect effect on the relationship between fear of COVID-19 and intention to vaccinate against COVID-19 in the 13 countries assessed. Finally, the cross-national similarities of the mediational model among the 13 participating countries are strongly supported. The study is the first to test a cross-national mediational model across variables in a large number of Latin American countries. However, further studies with other countries in other regions of the world are needed.